Phenylene-bridged cross-conjugated 1, 2, 3-trisilacyclopentadienes. Issue 60 (12th July 2018) - Zhao, Hui; Klemmer, Lukas; Cowley, Michael J.; Majumdar, Moumita; Huch, Volker; Zimmer, Michael; Scheschkewitz, David
Abstract : Reaction of a cyclotrisilene, c-Si3 R4 (R = iPr3 C6 H2 ), with 1, 4-diethynyl benzene results in the cross-conjugated bridging of two 1, 2, 3-trisilacyclopentadiene moieties by para -phenylene. Abstract : 1, 2, 3-Trisilacyclopentadienes are obtained from the reactions of cyclotrisilene c-Si3 R4 (R = iPr3 C6 H2 ) with phenyl and diphenyl acetylene, respectively. With 1, 4-diethynyl benzene the cross-conjugated bridging of two of the Si3 C2 cycles by a para -phenylene linker is achieved. UV/vis spectroscopy indicates a small but significant effect of cross-conjugation, which is confirmed by TD-DFT calculations. The formation mechanism of the 1, 2, 3-trisilacyclopentadienes is elucidated by VT NMR.